Дослідження в середній течії р. Удай (матеріали до археологічної карти Пирятинського р-ну) - Головко, І.В. (Археологічні дослідження в Україні, 2010)
The paper presents a summary of the research in the middle flow of the Uday River (Sula’s basin) in Pyryatyn Region of Poltava Oblast in 2009. Eight sites not known before of various periods have been discovered. The great success was the discovery and description of the hill-fort of Scythian time near Kaplyntsi village and of an archaeological site of the Late Bronze Age near Pyryatyn.